Influence of geological faults on dissolved arsenic concentrations in an overexploited aquifer with shallow geothermal heat. (September 2022) - Piña González, Viridiana; Miranda Avilés, Raúl; Hernández Anguiano, Jesús Horacio; Knappett, Peter S.K.; Morales Martinez, Jorge Luis; Puy Alquiza, María de Jesús; Naves, Acacia; Bian, Jianmin; Liu, Jianli; Ramírez González, Lucía Magali; Navarro Céspedes, Juan Manuel; Li, Yanmei
Abstract: Hydrochemical and mineralogical analyses were performed to identify the main processes that contribute to the concentration of total inorganic arsenic (iAs) in groundwater within the northern portion of the Laguna Seca aquifer in Guanajuato State, Mexico. The spatial extent of the study area spans across a large graben with pore-waters that contain the highest dissolved arsenic concentrations in the basin. This scale of study was chosen to test the hypothesis that normal faults act as conduits for rising geothermal waters carrying arsenic into the shallow aquifer that has been historically depressurized by irrigation pumping. The arsenic content in outcrops ranged from 3.5 to 19.5 ppm. The major minerals are quartz, plagioclase, micas, and zeolites. Multivariate cluster and Principal Components Analyses on the chemical composition and temperature of 15 wells in the study area suggest that silicate weathering is the dominant water-rock interaction that explains the observed concentrations of major ions and arsenic in groundwater. The sampled irrigation and municipal wells ranged from 190 to 550 m in depth and had temperatures ranging from 28.3 to 45.2 °C. Cluster II had the highest temperature, and greatest mineralization (total dissolved solids), and it was more influenced by regional flow than Cluster I. The concentration of iAs ranged from 16 to 229 μgL −1, all of the samples exceeded the maximum concentration suggested by the World Health Organization (10 μgL −1 ). Four samples belonging to Cluster II exceeded the maximum concentration set by Mexican regulations (25 μgL −1 ) by at least five times. The highest concentration of arsenic in surface rock coincides spatially with Cluster II wells. Geothermal heat and long pore-water-residence times enables the dissolution of silicate minerals which increases the pH (from 7.3 to 9.1) and consequently drives desorption of arsenic from mineral surfaces. During the dry season the iAs content increased in all wells from 6 to 138 μgL −1 compared to the wet season. This could be attributed to the increase in pumping that occurs then. The close proximity of Cluster II wells to newly mapped faults within the graben supports the hypothesis that Cluster II wells intercept regional groundwater flow that ascends through those previously unmapped faults. Graphical abstract: Image 1 Highlights: Silicate mineral dissolution increases pH and arsenic concentrations in groundwater. Buried normal faults were mapped using geochemical and remote sensing techniques. Geothermal waters ascend through vertical faults. Arsenic concentrations increase during the dry season due to increased irrigation pumping.